An institutional framework for enhanced food security amidst the COVID-19 pandemic: Strategic implementation and outcomes - Akbar Akbar; Rahim Darma; Andi Irawan; Letty Fudjaja; Riri Amandaria; Rida Akzar (Journal of Agriculture and Food Research)
The COVID-19 pandemic revealed significant vulnerabilities in Indonesia's food security system, highlighting the urgent need for an effective institutional framework to ensure food availability, accessibility, and stability. This study, a collaborative effort involving key institutions such as the Ministry of Finance, BAPPENAS (Ministry of National Development Planning Agency), and DPR (House of Representatives), examines strategic roles in addressing these challenges. The research uses an Interpretive Structural Modelling (ISM) approach to identify key institutional drivers, constraints, and policy mechanisms crucial for enhancing food security. The data, gathered through in-depth interviews and focus group discussions with institutional stakeholders from Indonesia's agricultural sector, underscore the critical role of institutional coordination in strengthening resilience, fostering cross-sectoral collaboration, and improving crisis response mechanisms. The findings highlight the pivotal roles of key institutions in strategic budget allocation, policy formulation, and legislative oversight, enhancing stakeholder commitment and program credibility. However, financial constraints, supply chain disruptions, and inadequate investment in agricultural innovation remain significant challenges. The research offers policy recommendations to address the barriers, including prioritizing budget allocations for agricultural development, improving stakeholder collaboration, and promoting research and innovation. By strengthening institutional synergy and fostering public-private partnerships, we can mitigate future food security risks, reduce vulnerabilities, and create a more adaptive, inclusive, and sustainable food security system in Indonesia.